Left ventricle remodeling by CMR in treated patients with primary aldosteronism and primary systemic arterial hypertension. - Carolina S Reiser; Antonildes N Assuncao; Jose A B Araujo-Filho; Roberto N Dantas; Luiz A Bortolotto; Jose R Parga-Filho (PLoS ONE)
Background Increased cardiac after load and multiple non-hemodynamic stimuli implicate in adverse left ventricular remodeling (LVR). This is particularly identifiable in treatment-resistant and secondary hypertension contexts, like primary hyperaldosteronism (PA), however little data exists on post-treatment residual LVR in these individuals. Methods Cardiac magnetic resonance (CMR) with T1 mapping were performed in 14 patients with treated PA matched with 15 treated patients with primary hypertension (PH) and 15 healthy individuals. Blood pressure (BP) control was defined as < 140 x 90mmHg. Results Treated PA and PH patients had similar indexed left ventricular, extracellular matrix and intracellular masses (respectively 68 ± 12g/m2, 17 ± 3g/m2 and 52 ± 10g/m2 for PA vs 63 ± 18g/m2, 16 ± 5g/m2 and 47 ± 14g/m2 for PH, p > 0.05 for all), that were significantly higher than normal individuals (47 ± 8g/m2, 11 ± 2g/m2 and 36 ± 6g/m2, respectively, p < 0.05 for all). Patients with uncontrolled BP exhibited greater cardiomyocyte hypertrophy than those controlled (55 ± 11 g/m2 vs 43 ± 11 g/m2, p = 0.01), regardless of the cause of hypertension. PH individuals had strong correlations between BP measurements and LVR parameters of the CMR, while in PA correlations were weaker. Conclusions In treated patients with PA and PH, CMR detected similar residual tissue LVR in both groups. Uncontrolled BP was more related to the observed LVR than to the etiology of hypertension. BP levels were more strongly correlated to CMR LVR parameters in PH than PA patients.